PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 (Studi Kasus di SMPK 3 Yos Soedarso Blitar) - Wiharti, Marcellina Alma; Widiatna, Alexius Dwi (CREDENDUM: Jurnal Pendidikan Agama, 2022)
Covid-19 has had an impact on all aspects of life, including education. The temporary closure of educational institutions is an effort to break the chain of the spread of the Covid-19 virus. However, there are obstacles in the learning process such as the lack of readiness of gadget facilities and the uneven distribution of the internet network in several regions in Indonesia. Lack of interaction between teachers and students and the cultivation of character in students. So that it has an impact on the weak sense of honesty and discipline of students in participating in online learning. This must be overcome so that learning that runs in the midst of the Covid-19 pandemic remains in accordance with existing regulations. Researchers used a qualitative case study method by exploring how the online learning process at SMPK 3 Yos Soedarso Blitar. Data obtained by collecting interviews, researchers interviewed teachers, parents, and students. Researchers are also involved in exploring online learning activities that take place. The results of this study are, schools have high readiness in the online learning process during the Covid-19 pandemic, teacher-student interactions are quite well established, teachers provide appropriate learning materials and assignments, and parents and teachers continue to instill character values ​​in students self. In the current Covid-19 pandemic, students must have a high sense of discipline and honesty in participating in online-based learning.